Preliminary study of the fibrin structure in hypertensive, dyslipidemic and type 2 diabetic patients. - Marchi Cappelletti, Rita; Suárez Nieto, Nuris (Investigación Clínica, 2013)
Â Individuals with hypertension, dyslipidemia or diabetes are at a higher risk to suffer cardiovascular disease than other people; while impaired fibrin structure/function may contribute to further raise the cardiovascular risk in the former. The purpose of this work was to study the fibrin network and fibrin degradation properties in hypertensive (HT) patients, pharmacologically treated, 124 Ó 11 mmHg, systolic blood pressure, and 70 Ó 10 mmHg, diastolic blood pressure, n = 12; metabolic dyslipidemic patients (DL), cholesterol: 5.7 Ó 1.5 mmol/L, n = 10; patients with type 2 diabetes mellitus (T2D), fasting plasma glucose: 8.8 Ó 2.2 mmol/L, n = 10; and a control group of healthy individuals, n = 9. The fibrinogen concentration was determined by the gravimetric method. Fibrin network formation and porosity were assessed by turbidity and permeation techniques, respectively; fibrin elastic properties were evaluated by compaction and fibrin lysis, by turbidity after addition of external tPA prior to plasma clotting. Fibrinogen concentration was significantly higher only in T2D patients (p = 0.004), compared to the control group. The fibrin polymerization and lysis processes were similar for all patient and control groups. Permeation was significantly slower in DL and T2D patients, p = 0.022 and 0.0002, respectively, whereas the compaction coefficient was significantly smaller in T2D patients, p = 0.0015. Our results suggest that the fibrin structure was altered in DL and T2D patients, probably due to the increased cholesterol and glycation, respectively.